Numerical Investigation on the Effect of Fuel-Rich Degree in the RBCC Engine under the Ejector Mode - Yizhi Yao; Mingbo Sun; Menglei Li; Peibo Li; An Bin; Rui Gu; Jiaoru Wang; Feng Wei; Taiyu Wang; Jikai Chen (International Journal of Aerospace Engineering)
The ejector mode of the Rocket-Based Combined-Cycle (RBCC) engine is characterized by high fuel consumption. This study is aimed at investigating the influence of the rocket fuel-rich degree on the RBCC engine’s performance under the ejector mode combined with simultaneous mixing and combustion (SMC). Numerical simulations were conducted for various rocket mixing ratios (Φ=1.6~3.2) under subsonic (Maf=0.9) and supersonic (Maf=1.8) flight conditions. It was observed that a high fuel-rich degree in the rocket plume negatively impacts the eject performance under all conditions. However, it improves the overall performance (Isp) at high flight Mach numbers (Maf). For supersonic conditions, increasing the fuel-rich degree promotes greater fuel participation in combustion, thereby enhancing RBCC engine performance. Nevertheless, the subsonic-supersonic mixing layer exhibits low evolution, resulting in a decrease in reaction efficiency from 29.2% to 12.0% as the Φ decreases from 3.2 to 1.6. Consequently, there is an inefficient utilization of fuel. To optimize RBCC engine performance, the rocket fuel-rich degree can be appropriately increased. However, this increase should be limited to prevent fuel wastage arising from low reaction efficiency. Under subsonic conditions (Maf=0.9), the low kinetic energy of captured air leads to the occurrence of “negative thrust surface” and “wall impact” phenomena, which hinder the efficient and stable operation of the RBCC engine. Consequently, adjusting the fuel-rich degree alone cannot promote specific impulse (Isp), and a low fuel-rich degree is considered an ideal strategy when combined with adjustable nozzle technology.